RANCANG BANGUN PENDETEKSI TINGKAT KEHIJAUAN WARNA DAUN PADI MENGGUNAKAN SENSOR WARNA TCS230 - Hidayat Hidayat; Yazid Baihaqy (Jurnal Teknologi Terapan, 2022)
Fertilization of rice plants according to the dose of their needs is one of the important things to produce an optimal rice harvest. Giving less or more fertilizer can cause rice plants not to grow optimally and even cause crop failure. The need for fertilizer doses can be determined by changing the color of the rice leaves using the Leaf Color Chart (LCC). However, obstacles in the field are challenging for novice farmers to predict fertilizer needs just by looking at the color of the leaves with the naked eye. The application of information technology is expected to help farmers, especially novice farmers, in measuring the dose of fertilizer needed for rice plants. The technology that will be applied is an electronic device that can detect the color of rice leaves and provide information for users from the measurement results through an android application on a smartphone device. The electronics modules used are the TCS320 color sensor module which functions to detect the color of objects, the Arduino UNO microcontroller module which contains ATMega128 as a data processor, and the Bluetooth module as a communication liaison between the microcontroller device and the android application on the smartphone. The test results show that the built device can function properly. All tested leaves can be classified according to the greenish level of the leaf color.